An Industrial quality control study of Cardinal Ceramics - Deriada, Gerard John (College of Engineering, 2001)
Cardinal Ceramics started as a company aiming to help people afflicted with Hansen's disease (leprosy) and their relatives be more productive members in the community of Tala, Kalookan. The company produces ceramic ware particularly gift ware, dinnerware, and oven ware. This apper is about the Industrial Quality Control of Cardinal Ceramics particularly their ovenware. Data were gathered through historical records, interviews with key personnel and direct observation. After the month long visits, the problems identified by the main problems identified by the group are : kiln dropping, iron spots, pinholes and bubbles. The main causes of the identified problems were determined with Ishikawa Diagram. It was found out that excess glazed clay was the cause of kiln dropping, dirty handling was the primary cause of iron spots, excessive polishing of the ware and improper aging of the clay were the main causes of pinholes, and excessive moisture in the ware was the cause of bubbles. The control limits for each problem was determined based on the May 2000 record of the company. The control charts showed that the processes, which caused kiln droppings, pinholes, and bubbles were out of control. For the iron spots, it showed that the defect was inherent to the process. The Process Capability Analysis were made with the use of the process capability ration. From the analyses, the processes for kiln droppings and iron spots are incapable, and the processes for pinholes and bubbles are capable. It has the same conclusion as the Statistical Quality Control Analyses. For the Kiln droppings it was recommended that the glaze be regulated and oven br cleaned after every production. The clay should be hardened tominimize iron spots. Control of polishing and inspection of clay were the recommendations to avoid pinholes. The aging period per batch should be recorded and the excess polish be measured and tabulated. For bubbles, it is recommended to implement strict draining schedule of the rampress and check the proportions of chemical ingredients properly before mixing them into the clay. It is also possible to have the automatic draining function of the machine be repaired. Also for bubbles, it is recommended that the water content be recorded to know its tolerance of moisture before bubbles occur.